FAR-FETCHED PROPERTIES OF VARUN MOOLA (CRATAEVA NURVALA ROOTS) & PALASHPUSHPA (BUTEA MONOSPERMA FLOWERS) TO MANAGE UROLITHIASIS - Poonam, *Mohod; Sharad, Mohod; Thapa, Anuradha (International Journal of Ayurveda and Pharma Research, 2016)
Urolithiasis is a worldwide problem having no sparing with any group like geographical, cultural or racial. Urinary calculi may cause obstruction, hydronephrosis, infection and hemorrhage in the urinary tract. The management of Urolithiasis with the procedures like surgery, lithotripsy and laser therapy were not only costly but also their recurrence rate are uncertain. But Ayurveda can be the good option to fill this gap with good results. Hence it is necessary and need to explore an Ayurvedic preparation which can resolve this problem with accurate results. And Varun roots and Palash flowers Kwath will be the best option to manage Urolithiasis. Present study was carried out on 30 patients suffering from Urolithiasis. It was a single blind clinical study to evaluate the efficacy of Varun Moola and Palashpushpa Kwath by subjective and objective criteria. 40 ml mixture of decoction was given twice daily for 30 days or till symptoms relieved whichever is earlier. The study revealed that there were significant and positive results of the applied drugs found on the management of Urolithiasis due to its diuretic, anti-infective, anti-biotic and anti-inflammatory properties. These drugs not only reduces symptoms like pain, dysuria, nausea, vomiting, and burning micturition but also helps to reduced pus cells and RBCs in urine as well. This contributes to control urinary tract infection resulting to cure Urolithiasis without producing any adverse effects on patients.